Formulation and in vitro evaluation of berberine containing liposome optimized by 32 full factorial designs - Girish Sailor,A K Seth,Ghanshyam Parmar,Sachin Chauhan,Ankur Javia (Journal of Applied Pharmaceutical Science, 2015)
The present study demonstrates the application of 32 full factorial design for optimization of berberine loaded liposome for oral administration. Thin film hydration method was used to prepare liposome and optimization was done by 32 full factorial designs combined with desirability function. Nine formulations were prepared by using different drug : lipid and soyphosphatidylcholine : cholesterol (SPC:CHOL) ratios and evaluated for entrapment efficiency and vesicle size. The statistical validity of model was done by analysis of variance (ANOVA). Response surface graph and contour plots were used to understand the effect of variables on responses. The optimized formulation with 0.782 desirability value was prepared and evaluated for responses. The results of entrapment efficiency and vesicle size were found to be very close with the predicted values. In addition, an optimized formulation was also characterized for zeta potential, in vitro drug release and morphology. The formulation was found to be spherical shape with an average diameter of 0.823 nm and -1.93 mV zeta potential and also shows sustained release pattern. These results support the fact that 32 full factorial designs with desirability function could be effectively used in optimization of berberine loaded liposome.
Keywords: Berberine, 32 full factorial design, desirability function,lipid based formulation.